Images and meanings in the discourse of the press media on a benzene occupational intoxication epidemic - Maria Ligia Rangel-S; Cassandra Schally (Faculdade de Medicina de Botucatu (Unesp), 2006)
The study analyses the construction of a certain public image, as built by four daily newspapers published in Salvador-Bahia-Brazil, for the different social actors involved in a public debate, during a benzene occupational intoxication epidemic, which affected workers from the Petrochemical Complex of Camaçari-Bahia-Brasil (COPEC), during the years of 1990 and 1991. This study uses references applied by the Symbolic Interactionism perspective, mainly coming from Erving Goffman, one of the most expressive sociologists in this research area, enabling the analysis of discourses contained in the newspapers by using the analytical categories: "voice", "footing" and "face" on 30% of the journalistic material published, during eighteen months. The analysis revealed the building of hesitating, conflicting and docile "faces", which occurred due to the dynamic variations in which the social actors were displayed and how they were put to operate in the text. The texts build up a variety of public images for petrochemical complex workers, for employers of COPEC and for governmental representatives.